PENGGUNAAN ANALISIS STRATEGIS DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM (LPI) : PENDEKATAN SWOT, BSC, DAN SIX SIGMA - Haris, Abdul; Marsya Aulia Rahman; Widya Amelia Putri; Muhammad Detiar (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2025)
The management of Islamic Education Institutions (LPI) faces increasingly complex challenges along with technological developments, social changes and the demands of globalization. To answer this challenge, strategic analysis approaches are important in ensuring LPI's sustainability and efficiency. This article discusses the use of three strategic analysis methods, namely SWOT (Strengths, Weaknesses, Opportunities, Threats), BSC (Balanced Scorecard), and Six Sigma, in LPI management. This approach aims to provide comprehensive insight for LPI managers in improving the quality of education and management effectiveness. The research results show that a combination of these three approaches can produce a more effective planning strategy in realizing LPI's vision and mission